Overtime Work, Overtime Compensation and the Distribution of Economic Well-Being: Evidence for West Germany and Great Britain - Markus Pannenberg; Gert G. Wagner (Institute for the Study of Labor (IZA), 2001)
Using panel data for West Germany and Great Britain, we show that there are striking differences in overtime work and overtime compensation in the two countries in the 1990s. Our estimates reveal that the observed overtime patterns affect both the evolution of the monthly labour earnings distribution and individual economic well-being differently in West Germany and Great Britain. Besides varying labour market institutions in the two countries a higher incidence of a combination of performance-related pay and unpaid overtime in Great Britain is an important factor in explaining the observed differences. With regards to West Germany, we show that the current policy of transforming paid overtime in ?working time accounts?, which is conducted in the spirit of ?work-sharing?, is neither beneficial for employed workers in terms of income mobility, nor in terms of overall job satisfaction nor in terms of working time preferences.
Keywords: J22; J33; J23; J31; 330; Overtime; wage inequality; economic well-being; semi-parametric decomposition technique; panel data; Überstunden; Lohn; Arbeitszeitflexibilisierung; Einkommenseffekt; Beschäftigungseffekt; Schätzung; Vergleich; Deutschland; Großbritannien